Epistolary Heritage of Ivan Lypa. Review of the book: Correspondence of Ivan Lypa (1892–1922) / compl. Ihor Stambol. Kyiv : Tempora, 2020. 576 p - Vovk, Olga (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2021)
Epistolary Heritage of Ivan Lypa. Review of the book: Correspondence of Ivan Lypa (1892–1922) / compl. Ihor Stambol. Kyiv : Tempora, 2020. 576 p